(untitled) (Educational Dimension, 2022)
Computer simulation and modeling are now widely used in computer science teaching. There are various approaches to make the educational process more efficient. Visualization is one of them, and the flipped classroom approach is another. The goal of this research is to show how to improve the efficiency of teaching data structures (hashing, trees) in the Algorithms and Data Structures course. We conducted two tests with four study groups of second-year bachelor students in two Algorithms and Data Structures subjects – (1) Hashing, (2) Trees (BST, RBT, AVL). In the first experiment, study groups on subjects (1) and (2) were formed using the same type of teaching technique, either with or without visualization tools. In contrast to the first experiment, we employed flipped classroom approaches for one study group and a traditional teaching method for the other.